HOMOLOGY BASED 3D- STRUCTURE MODELING OF AQUAPORIN-2 PROTEIN - MONICA SONI,; ARVIND PAREEK, (International Journal of Pharma and Bio Sciences, 2014)
The aquaporin-2 (AQP2) water channel plays an important role in re-absorption of water in the kidney collecting duct and consequently in concentrating urine. Mutations in AQP2 can cause to disorder such as nephrogenic diabetes insipidus, congestive heart failure, liver cirrhosis, renal cystic disease, etc. Homology modeling allows building three-dimensional protein structure models using experimentally determined 3D-structures of related homologus protein as templates. In this study, it is assumed that the 3-D structure of the protein aquaporin-2 gave the structural analysis. That’s why; we modeled the 3-D structure of aquaporin-2 with Swiss - Model by using the crystal structure of Aquaporin-2 as the template. Template AQP2 search with Blast and HHBlits has been performed against the SMTL and have highest identity sequence comparatively others template sequence. Its 3-D structure, obtained from this modling, was evaluated and validated by using PSVS. 3D- structure of human AQP2 protein structure is only reported in a minority of missense mutation cases in the nephrogenic diabetes insipidus.